Békesség Istennel / Billy Graham / [kiad. a Magyarországi Szabadegyházak Tanácsa] / [ford. Gerzsenyi László]. - Graham, Billy, 1918-2018. (Budapest : Magyarországi Szabadegyházak Tanácsa, 1985)
Dr. Graham shares God's gentle reassuring promise of spiritual calm-of authentic spiritual peace-amidst a personal life wracked with too much stress, too many burdens, too great a heart-ache period. Drawing from Romans 5:1, "Therefore being justified by faith, we have peace with God through our Lord Jesus Christ," Dr. Graham addresses such issues as: After Death-What?, Why Jesus Came, What is Faith, Hope for the Future, and Peace at Last. With quiet confidence and surefooted faith, Billy Graham points unerringly toward the One who is the only dependable source of the peace that passes understanding. Both comforting and challenging, this classic explanation of the human predicament and the divine answer has been changing lives for generations.
Original title: Peace with God.
HU OSA 430 - Donation of Zsuzsa Horváth
Keywords: Theology, Doctrinal -- Popular works; Christian life -- Baptist authors